2007
DOI: 10.2106/jbjs.f.00601
|View full text |Cite
|
Sign up to set email alerts
|

Navigated Total Knee Replacement

Abstract: Navigated knee replacement provides few advantages over conventional surgery on the basis of radiographic end points. Its clinical benefits are unclear and remain to be defined on a larger scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
203
3
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(220 citation statements)
references
References 35 publications
7
203
3
7
Order By: Relevance
“…Although we did not see statistically significant differences in our series except for the postoperative leg alignment the authors recommend the use of a navigation system because of the described advantages such as better leg alignment and better component orientation [3,27]. Our study has some limitations.…”
Section: Discussioncontrasting
confidence: 59%
“…Although we did not see statistically significant differences in our series except for the postoperative leg alignment the authors recommend the use of a navigation system because of the described advantages such as better leg alignment and better component orientation [3,27]. Our study has some limitations.…”
Section: Discussioncontrasting
confidence: 59%
“…Studies were included if they were randomized controlled trials (RCT) or quasi-randomized controlled trials, or if they used non-randomized prospective cohorts and historical cohorts [24].…”
Section: Selectionmentioning
confidence: 99%
“…A previous meta-analysis [6] evaluated the radiographical outcomes after computer-navigated knee arthroplasty was performed and found a reduction in outlier rates for the mechanical leg axis. Another two meta-analyses [13,67] showed that the computer navigation system improved component orientation and mechanical axis of the lower limb in TKA.…”
Section: Introductionmentioning
confidence: 99%